Indications for Mode of Delivery in Pregnant Women with Inflammatory Bowel Disease. Issue 5 (14th April 2017) - Burke, Kristin E.; Haviland, Miriam J.; Hacker, Michele R.; Shainker, Scott A.; Cheifetz, Adam S.
Abstract : Background: Reasons for the increased incidence of cesarean delivery among women with inflammatory bowel disease remain unclear. We assessed cesarean delivery incidence and factors influencing mode of delivery in women with inflammatory bowel disease. Methods: We performed a 10-year retrospective cohort study of nulliparous women who delivered a singleton infant at our institution. We compared the risk of each mode of delivery in women with Crohn's disease and ulcerative colitis with women without inflammatory bowel disease. We assessed mode of delivery indications for patients with inflammatory bowel disease and whether cesarean deliveries were planned. Results: The overall incidence of cesarean delivery among women with Crohn's disease (24/59; 40.7%) was similar to that among women without inflammatory bowel disease (7868/21, 805; 36.1%) (risk ratio 1.1 [95% confidence interval, 0.83, 1.5]; P = 0.46), but was increased in the subgroups with active and inactive perianal disease (risk ratio 2.3; P < 0.01). Women with ulcerative colitis had a 1.8-fold increased relative risk of cesarean delivery (41/65; 63.1%) (95% confidence interval, 1.5, 2.1; P < 0.01), with highest incidence in patients with ileal pouch-anal anastomosis. Forty-nine percent of ulcerative colitis and 66.7% of Crohn's disease cesarean deliveries were unplanned, with only 1 unplanned delivery performed for active inflammatory bowel disease. Most unplanned deliveries were for arrest of descent/dilation and nonreassuring fetal heart tracings. Seventy-five percent of planned cesarean deliveries were for inflammatory bowel disease–related indications. Conclusions: Women with ulcerative colitis and perianal Crohn's disease have an increased incidence of cesarean delivery. At least half of cesarean deliveries are unplanned.